2011
DOI: 10.4317/medoral.16.e584
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of a new hemostatic agent on human pulp fibroblasts in vitro

Abstract: Objective: The objective of this study was to evaluate the cytotoxicity of the plant extract ankaferd blood stopper (ABS) in vitro. Study Design: ABS was eluted with fresh Dulbecco's Modified Eagle's Medium (DMEM) without serum for 72 h, at 37°C. The cells treated with various dilutions of ABS were seeded into 96-well microplate at 10 4 /well in triplicates. Cells without treatment served as a control group. The number of viable cells after 48 h incubation was determined by a modified 3-(4, 5-dimethyl-thiazol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…Therefore, there are molecular links underlying ABS-pleiotropic cellular actions acting on anti-infective [30][31][32] , wound healing 2,[33][34][35][36] , and apoptotic processes. 22,23 Since myeloma is located at the crossroads of cellular neoplastic development and M-protein secretion, the unique effects of ABS on distinct clonal paraproteins shall be investigated in future in vivo animal models mimicking plasma cell disorders. Our present study represent true basis for the design of such trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there are molecular links underlying ABS-pleiotropic cellular actions acting on anti-infective [30][31][32] , wound healing 2,[33][34][35][36] , and apoptotic processes. 22,23 Since myeloma is located at the crossroads of cellular neoplastic development and M-protein secretion, the unique effects of ABS on distinct clonal paraproteins shall be investigated in future in vivo animal models mimicking plasma cell disorders. Our present study represent true basis for the design of such trials.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][15][16][17][18][19][20] ABS has many cellular effects. 1,[21][22][23] ABS has been shown to affect renal tubular apoptosis based on the level of hemorrhage. 22 When the bleeding associated with the surgery of partial nephrectomy is mild or moderate, ABS can initially increase renal tubular apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are molecular links underlying ABSpleiotropic cellular actions acting on anti-infective, wound healing, and apoptotic processes. 1,6,7,10,13,17,[24][25][26][27][28][29][30][31][32] Since renal system is located at the crossroads of cellular neoplastic development and protein secretions, the unique effects of ABS on distinct renal cell types shall be investigated in future in vivo animal models mimicking cancer models. Our present study represent true basis for the design of such experimental animal trials.…”
Section: Discussionmentioning
confidence: 99%
“…16 Moreover, a recent study suggested in vitro ABS cytotoxicity on the human pulp fibroblasts. 17 Therefore, ABS effects on the tissue level should also be searched after its topical usage in the injury models. The aim of this experimental study was to assess short-and mid-term topical kidney safety following the topical administration of ABS in rats.…”
mentioning
confidence: 99%
“…In a recent study, Odabaş et al [27] found that ABS was cytotoxic to human pulp fibroblasts. The sensitivity of cytotoxicity depended on the concentration of the material tested.…”
Section: Ankaferd Blood Stoppermentioning
confidence: 97%